First Molecular Survey and Genetic Characterization of Rickettsia spp. in Haemaphysalis hystricis Ticks Infesting Dogs in Taiwan - Chien-Ming Shih; Xing-Ru Huang; Esmeralda Erazo; Li-Lian Chao (Microorganisms, 2025)
Rickettsia infection in Haemaphysalis hystricis ticks infesting dogs was first screened in Taiwan by nested-PCR assay targeting the citrate synthase gene (gltA) of Rickettsia. A general infection rate (3.46%) was detected in a total of 1186 examined ticks, and infection rates of 3.20%, 3.6%, and 4.27% were detected in females, males, and nymphs, respectively. The monthly prevalence of Rickettsia infection was observed from March to November, and the highest infection was detected in April (6.92%) followed by a higher infection in July (5.56%), October (4.72%), September (3.57%), and May (3.54%). The prevalence of Rickettsia infection in ticks infesting stray dogs (4.15%) is significantly higher than ticks infesting domestic dogs (1.11%) (chi-square test, p = 0.015). Genetic analysis based on the gltA gene sequences from 13 Taiwan specimens, compared with 13 genospecies of Rickettsia strains documented in GenBank, revealed that the genetic identities of these Taiwan strains were phylogenetically affiliated with the genospecies of the transitional group (R. felis) and the spotted fever group (R. aeschlimannii and R. raoultii) of Rickettsia. This study demonstrates the first molecular screening of Rickettsia spp. in H. hystricis ticks infesting dogs in Taiwan. The human pathogenic strain of R. aeschlimannii was first discovered in H. hystricis ticks infesting dogs. Because dogs serve as companion animals to humans, the presence of various Rickettsia species existing in H. hystricis ticks may pose a potential threat to human health in Taiwan.